PSYCHOLOGICAL HANDLING OF FORMER DEVIAN WITH ISLAMIC EDUCATION AT PASURUAN METAL PESANTREN - Malikah, Malikah (Journal of Contemporary Islam and Muslim Societies, 2023)
Abstract: The deviation is deviant behaviour that hurts the perpetrator, family, and society. The former deviant who wanted a better life after coming out of the abyss of darkness did not get a proper place. Unlike other rehabilitation institutions, the Pasuruan Metal Pesantren offers a pattern of psychological treatment for former deviants with religious education. This study uses a qualitative approach with interviews and observations as data mining in the field. By using physical therapy (such as Wudu’, prayer, writing the Qur’an, and morning exercises) and spiritually (such as reading and memorising the Qur’an, dhikr assemblies, prayers, religious lectures, and taklim assemblies), former Devian can recover and return to her family and society as before.Keywords: Devian, Psychology, Pesantren, Religious therapy.